1978
DOI: 10.1111/j.1365-2125.1978.tb01596.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of combined oral theophylline and inhaled beta‐adrenoceptor agonist bronchodilator therapy.

Abstract: 1. The bronchodilator effects of 500 microgram rimiterol by pressurized aerosol, 375 mg oral theophylline and both drugs in combination were compared in a randomized, placebo‐controlled, double‐blind trial in eight patients with chronic, partially reversible airways obstruction. 2. The four treatments were (i) oral theophylline, placebo aerosol (TP); (ii) oral placebo, rimiterol aerosol (PR); (iii) oral theophylline, rimiterol aerosol (TR) and; (iv) oral placebo, placebo aerosol (PP). The aerosol was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…A higher frequency of side effects was observed qualitatively with use of the combination or terbutaline, as compared to oxtriphylline. Similar results were obtained from a study by MARLIN et al [60] where theophylline was combined with another specific beta2-bronchodilator, rimiterol. These authors demonstrated that oral theophylline interacted with aerosolized rimiterol in an additive fashion to reverse bronchospasm in eight asthmatics.…”
Section: Evidence Contrary To Combination Synergismsupporting
confidence: 89%
“…A higher frequency of side effects was observed qualitatively with use of the combination or terbutaline, as compared to oxtriphylline. Similar results were obtained from a study by MARLIN et al [60] where theophylline was combined with another specific beta2-bronchodilator, rimiterol. These authors demonstrated that oral theophylline interacted with aerosolized rimiterol in an additive fashion to reverse bronchospasm in eight asthmatics.…”
Section: Evidence Contrary To Combination Synergismsupporting
confidence: 89%
“…Its possible interaction with f2-adrenoceptor agonists has not yet been fully explored either at molecular level (Miech & Lohman, 1975;Trembath & Shaw, 1978) or in patients with airways narrowing. Conventional doses have been shown to have some additive effect when combined in asthmatics (Campbell, Middleton, Mackenzie, Shetter, McHardy & Kay, 1976;Wolfe, Tashkin, Calvarese & Simmons, 1978;Marlin, Hartnett & Berend, 1978) but these studies are incomplete since they ignore both individual differences in response and in theophylline clearance. The majority of patients attending our clinic have severe chronic bronchitis, leading to considerable loss of time from work.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Both single dose and steady state pharmacokinetic studies have been performed with these formulations and indicate that approximate peak serum theophylline levels will occur at 2 h with rapid release and 4 to 6 hs with slow release theophylline (Marlin, Hartnett, Berend & Hacket, 1978;McDevitt, Elwood & Russell, 1979;Svedmyr et al, 1979). Although both interpatient and intrapatient variability in the rate of drug absorption will occur, it is considered that these sampling times would provide an estimate of peak serum theophylline for a clinical monitoring survey in a large group of patients when a single sampling time is desirable practice.…”
Section: Discussionmentioning
confidence: 99%